150 Engagement to Reduce COVID-19 Vaccine Hesitancy - The Value of Investments In Long Term Community Relationships. (April 2022) - Nease, Donald; Tamez, Montelle; Barrientos-Ortiz, Charlene; Fisher, Mary; Brewer, Sarah; Zittleman, Linda
Abstract : OBJECTIVES/GOALS: The Colorado Community Engagement Alliance Against COVID-19 Disparities (CO-CEAL) Team has worked with 5 racial/ethnic communities in Colorado to understand COVID-19 vaccine hesitancy and develop messages, materials and dissemination strategies to impact vaccine hesitancy. Relationships have been key facilitators of this work. METHODS/STUDY POPULATION: CO-CEAL was funded for one year as a part of the national CEAL Teams effort. CO-CEAL engaged urban Hispanic/LatinX, rural Hispanic/LatinX, urban African/American, rural African Immigrant and urban American Indian/Alaska Native communities through Community Connectors in each community. Our Community Connectors led recruitment of community members for our community survey data collection (goal of 200 surveys from each community) and participation in our 5 Community (Boot Camp) Translations. Where possible we worked with Community Connectors and leveraged community relationships with whom we had worked over multiple years and projects. In two communities we worked to quickly build and establish new relationships with Community Connectors and their communities. RESULTS/ANTICIPATED RESULTS: The rapid nature of the CO-CEAL project, its timeline and the unusual nature of the funding mechanism required adaptations to usual ways of working on both the academic and community side.In our CO-CEAL partner communities where there was a history of working together, concerns, possible barriers and other issues tended to be rapidly addressed. The prior existing, long-standing relationships fostered trust that enabled open airing of concerns and an ability to address issues as they arose. In CO-CEAL partner communities where new relationships were being forged, trust needed to be build from the ground up. This made adaptations more challenging and the ability to address concerns and issues as they arose more problematic. Although the work has moved forward in all communities, extra care has been required in some. DISCUSSION/SIGNIFICANCE: When crises necessitate rapid action in communities, the depth of prior investments in building and maintaining relationships makes a difference in how rapidly and successfully partners can work together to address a crisis like the COVID-19 pandemic. Funders and Academic researchers should invest broadly in communities to enable rapid responses.